1981
DOI: 10.1029/ja086ia13p11111
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of electrons by interplanetary shocks

Abstract: Although proton acceleration often is observed at interplanetary shocks, electron acceleration rarely has been reported. In contrast, many of the shocks identified so far by instruments on the ISEE 3 spacecraft show significant increases in the spin averaged electron flux at energies greater than 2 keV. At 2 keV, the spin averaged electron flux usually increased by a factor of 2 to 3 but on several occasions increased to more than 10 times its preshock level. Often, the behavior of the electrons is similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 23 publications
6
33
1
Order By: Relevance
“…Armstrong & Krimigis 1976;Potter 1981;Sarris & Krimigis 1985;Lopate 1989). A characteristic feature of such accelerated electrons is a beam-like structure, which involves localisation in velocity space not only in the beam direction, but also in beam speed, with a gap between the speeds of thermal electrons and the beam particles.…”
Section: Introductionmentioning
confidence: 99%
“…Armstrong & Krimigis 1976;Potter 1981;Sarris & Krimigis 1985;Lopate 1989). A characteristic feature of such accelerated electrons is a beam-like structure, which involves localisation in velocity space not only in the beam direction, but also in beam speed, with a gap between the speeds of thermal electrons and the beam particles.…”
Section: Introductionmentioning
confidence: 99%
“…Bidirectional flow (but without loss cones) of protons as well as electrons were also observed by Potter (1981) upstream of quasi-perpendicular shocks. Figure 8 shows the angular distribution of 2 keV electrons just prior to the arrival of a shock on 1979 July 26.…”
Section: Bidirectional Distributionsmentioning
confidence: 90%
“…This mechanism involves (1) energization of electrons by the outwardpropagating coronal or IP shock, either due to reflection at the shock into upstream regions or due to the leakage from the heated downstream into upstream regions, (2) excitation of Langmuir waves through electron streaming instabilities, and (3) conversion of Langmuir waves into escaping radiation at f pe and 2f pe . In addition, the energetic electron flux enhancements as well as the Langmuir wave occurrences do not show any relationship with either the shock normal angle B n or the fast magnetosonic Mach number M ms (Potter 1981;Tsurutani & Lin 1985;Thejappa & MacDowall 2000). For example, Urbarz et al (1977) have suggested that the fluctuations in the type II burst fluxes are connected to the magnetic field and electron density fluctuations in the corona.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these observations show that (1) neither energetic electron (Potter 1981;Tsurutani & Lin 1985) nor Langmuir wave occurrence (Thejappa, MacDowall, & Vinas 1997;Thejappa & MacDowall 2000) is correlated with shock parameters, such as the shock normal angle B n and the fast magnetosonic Mach number M ms , (2) the site of type II burst excitation is probably located in the upstream regions (Lengyel-Frey et al 1997;Bale et al 1999;Thejappa & MacDowall 2000;Reiner et al 2000), and (3) the fragmentation of the type II radio bursts can be due to fluctuations in the efficiency of the conversion of Langmuir waves into escaping radiation (Thejappa & MacDowall 2001). Thejappa & MacDowall (2001) have suggested that fluctuations in the efficiency of linear coupling of Langmuir waves with the escaping radiation are probably responsible for the fragmentation.…”
Section: Introductionmentioning
confidence: 99%